Pengaruh Penggunaan Gadget Terhadap Perkembangan Kognitif Anak Usia Sekolah Dasar: Analisis Komparatif Dari Sudut Pandang Orang Tua dan Pendidik - Saharudin, Saharudin; Noviska, Della Wilza; Harsyah, Ahmad Syauqi (PAKAR Pendidikan, 2025)
The pervasive use of gadgets among elementary school-aged children has sparked concerns regarding its impact on cognitive development. This qualitative study delved into this issue by examining the experiences and perspectives of students at Cahaya Hati Islamic Elementary School through in-depth interviews over two months. Thematic analysis of the interviews shed light on the types and frequency of gadget use, contexts of usage, activities engaged in, and observed impacts on cognitive abilities. The findings revealed a significant reliance on gadgets for educational and leisure purposes, with implications for attention span and task focus. Drawing on theories of cognitive development, such as Piaget's constructivist perspective, Vygotsky's Zone of Proximal Development, and Bandura's Social Cognitive Theory, the discussion navigated the intricate interplay between gadget use and cognitive growth. Recommendations were formulated to optimize the benefits of gadget use while mitigating potential drawbacks, aiming to foster balanced cognitive development in children amidst the digital age.